COVID-19 and Food Security : Gendered Dimensions - Montalvao, Joao (World Bank, Washington, DC, 2020)
Across the developing world, the COVID-19 (Coronavirus) pandemic threatens to cause massive disruptions in food supply chains. The World Food Programme estimates that by the end of 2020, twu hundred and sixty five million will face acute food insecurity - twice as many as before the crisis. Women play a key role in keeping the food system functional. Their livelihoods also depend on these jobs, which are primarily concentrated in the informal sector, and they have little access tosavings andsocial safety nets. This note highlights women’s contribution to food supply chains, focusing on women as informal producers and traders of food. It discusses potential impacts of the pandemic on their vulnerabilities and policy responses. It concludes with some early reports on how women along the food supply chain are rising to the challenge of COVID-19 (Coronavirus), and some considerations for investments in inclusive food systems.